Higher Education and Wayward Labor Markets in Mexico - de Vries, Wietse; Cabrera, Alberto; Anderson, Shaquana (International Higher Education, 2009)
In an attempt to prepare students for the labor market using predictions on future employment trends, many Latin American institutions created new programs, systems, and incentives for unique, specialized majors, like nanotechnology and environmental design. These students seem to be having a harder time finding and feeling fulfilled by their work than many of their traditional-major counterparts. Shifting focus back to more broad, traditional courses of study such as law, civil engineering, and medicine may be challenging after two decades of contrary policy decisions.